HUBUNGAN KELINCAHAN DENGAN KETERAMPILAN DRIBBLING BOLA BASKET PADA SISWA KELAS VIII SMP NEGERI 43 PALEMBANG - Helen Purnama Sari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This study entitled Relationship of agility with basketball dribbling skills at students of Junior hight school 43 Palembang state, the purpose of this study was to determine the relationship of agility with basketball dribbling skills at students of Junior hight school 43 Palembang state. The method used in this study is the Correlation research method. This research is a type of associative research by looking for the relationship between agility of the body towards the ball dribbling skills in basketball games. The research variable is everything in the form that is determined by the researcher to be studied so that information about it is obtained, then conclusions are drawn, samples in the study there are 25 students. To process the test results, statistical steps are used which are guided by the product moment correlation formula with 1. Test the correlation coefficient, 2. Significance test, 3. Determination test.The results of this study are from the calculation results show that the relationship or correlation coefficient between agility (X) and dribbling skills (Y) is rxy = 0.725. To see the strength of the relationship between the two variables, the authors refer to the guidelines made by Sugiyono (2012: 231) where the value of 0.725 in the interval between 0.60 - 0.799 which states that the relationship between the two variables is strong and Based on existing calculations, then α = 0.05 and n = 23, two-party test dk = n - 2 = 25 - 2 = 23 so that t table = 1.714 is obtained. It turns out that tcount is greater than t table, or 5.0484> 1.714. Then Ho is rejected, meaning that there is a significant relationship between the relationship of agility with ball dribbling skills at students of Junior hight school 43 Palembang state. Keyword : Basketball, Agility, Dribbling skills.